Blended cement composition
A mixed cement composition with specific proportions of cement clinker, slag, and limestone powders addresses the need for reduced clinker usage and carbon emissions, enhancing initial strength development and sustainability.
Patent Information
- Application Number
- JP2021050600
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-03-24
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-03-24
AI Technical Summary
The cement manufacturing industry faces a challenge in reducing carbon dioxide emissions and the potential shortage of pulverized blast furnace slag powder, necessitating a cement composition that reduces cement clinker usage while maintaining strength development properties.
A mixed cement composition comprising cement clinker powder, pulverized blast furnace slag powder, and limestone powder, with specific proportions of each component, including a range of 47-59% cement clinker, 22-43% slag powder, and 4-23% limestone powder, along with controlled aluminate phase content, achieves reduced clinker usage and enhanced strength development.
The composition effectively reduces cement clinker usage, improving initial strength development and maintaining overall strength properties, while utilizing waste materials to enhance environmental sustainability.
Smart Images

Figure 0007619855000001 
Figure 0007619855000002 
Figure 0007619855000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a blended cement composition. [Background technology]
[0002] Currently, as part of measures to combat global warming, the cement manufacturing industry is being called upon to significantly reduce carbon dioxide emissions. Most of the carbon dioxide emissions in the cement manufacturing industry are generated during the production of cement clinker, and in order to reduce carbon dioxide emissions, there is a demand to reduce the production volume of cement clinker. As a cement that can reduce the amount of cement clinker used, blast furnace cement, in which part of the cement clinker powder is replaced with ground granulated blast furnace slag, is known. Patent Document 1 describes a cement composition using ground granulated blast furnace slag, which contains at least the following components (a), (b), and (c) in the following ratios: (a) Cements containing gypsum and ground cement clinker having a hydraulic ratio (HM) of 2.0 to 2.4, a silicate ratio (SM) of 1.3 to 3.0, and an iron ratio (IM) of 1.5 to 3.0: 20 to 50% by mass (b) Blaine specific surface area is 5,000 cm 2 / g or more blast furnace slag powder: 30 to 70 mass% (c) Limestone powder: more than 0% by mass to 40% by mass [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-254909 A Summary of the Invention [Problem to be solved by the invention]
[0004] Although ground granulated blast furnace slag has excellent qualities as a material to be mixed with cement, its production volume is not so large, and it is expected to become insufficient in the future. Therefore, there is a demand for cement that can reduce the amount of cement clinker powder used by replacing part of the cement clinker powder with materials other than ground granulated blast furnace slag. An object of the present invention is to provide a mixed cement composition which can reduce the amount of cement clinker powder used and has excellent strength development. [Means for solving the problem]
[0005] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned objects can be achieved by a powdery mixed cement composition comprising cement clinker powder, ground granulated blast furnace slag, and limestone powder, in which, relative to a total amount of 100 mass% of the cement clinker powder, ground granulated blast furnace slag, and limestone powder, the proportion of the cement clinker powder is 47 to 59 mass%, the proportion of the ground granulated blast furnace slag is 22 to 43 mass%, the proportion of the limestone powder is 4 to 23 mass%, and the proportion of an aluminate phase in the cement clinker powder is more than 13 mass% and 17 mass% or less, and have completed the present invention. That is, the present invention provides the following [1] to [4]. [1] A powdery mixed cement composition comprising cement clinker powder, ground granulated blast furnace slag, and limestone powder, wherein, in a total amount of 100% by mass of the cement clinker powder, ground granulated blast furnace slag, and limestone powder, the proportion of the cement clinker powder is 47 to 59% by mass, the proportion of the ground granulated blast furnace slag is 22 to 43% by mass, the proportion of the limestone powder is 4 to 23% by mass, and the proportion of an aluminate phase in the cement clinker powder is more than 13% by mass and 17% by mass or less. [2] The mixed cement composition according to [1], comprising 1.5 to 6.0 parts by mass of gypsum in terms of SO3 per 100 parts by mass of the cement clinker powder. [3] The mixed cement composition according to [1] or [2], wherein the cement clinker powder contains 54 to 63 mass% alite, 8 to 17 mass% belite, and 9 to 12 mass% ferrite. [4] The Blaine specific surface area of the limestone powder is 3,000 to 20,000 cm 2 The mixed cement composition according to any one of the above [1] to [3], wherein the mixed cement composition is a mixture of 0.1 to 0.5 g / g. [5] The mixed cement composition according to any one of [1] to [4], having a compressive strength of 33 MPa or more at 7 days as measured by the method described in "JIS R 5201:2015 Physical Testing Methods for Cement". Effect of the Invention
[0006] According to the mixed cement composition of the present invention, by using ground granulated blast furnace slag and limestone powder, the amount of cement clinker powder used can be relatively reduced, and strength development (particularly, initial strength development at an age of about 3 to 7 days) can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The mixed cement composition of the present invention is a powdery mixed cement composition containing cement clinker powder, ground granulated blast furnace slag, and limestone powder, in which, in a total amount of 100% by mass of the cement clinker powder, ground granulated blast furnace slag, and limestone powder, the proportion of the cement clinker powder is 47 to 59% by mass, the proportion of the ground granulated blast furnace slag is 22 to 43% by mass, the proportion of the limestone powder is more than 5% by mass and not more than 23% by mass, and the proportion of the aluminate phase in the cement clinker powder is more than 13% by mass and not more than 17% by mass. In this specification, the term "mixed cement composition" refers to a composition containing cement clinker powder, which is obtained by mixing a plurality of types of powdery materials.
[0008] In the total amount of cement clinker powder, ground granulated blast furnace slag, and limestone powder (100% by mass), the proportion of cement clinker powder is 47-59% by mass, preferably 49-58% by mass, more preferably 51-57% by mass, and particularly preferably 53-56% by mass. If the proportion is less than 47% by mass, the strength development is reduced. If the proportion exceeds 59% by mass, the amount of cement clinker powder in the mixed cement composition increases, and the effect of reducing the amount of carbon dioxide emissions associated with clinker production is reduced.
[0009] The proportion of the aluminate phase (3CaO·Al2O3) in the cement clinker powder is more than 13 mass% and not more than 17 mass%. The above ratio can increase the waste material unit (the proportion of waste-derived raw materials in the cement composition can be increased by using more waste as a clinker raw material) and, from the viewpoint of improving early strength development, is preferably 13.5 mass% or more, more preferably 14.0 mass% or more, and particularly preferably 14.2 mass% or more. In addition, from the viewpoint of further improving the fluidity and workability of mortar or the like containing the mixed cement composition, the above ratio is preferably 16.0 mass % or less, more preferably 15.5 mass % or less, and particularly preferably 15.2 mass % or less. The proportion of alite (3CaO·SiO2) in the cement clinker powder is preferably 54-63 mass%, more preferably 55-62.5 mass%, and particularly preferably 56-62 mass%. If the proportion is 54 mass% or more, the early strength development is further improved. If the proportion is 63 mass% or less, the fluidity and workability of mortar containing the mixed cement composition are further improved.
[0010] The proportion of belite (2CaO SiO2) in the cement clinker powder is preferably 8 to 17 mass%, more preferably 8.5 to 16 mass%, and particularly preferably 9 to 15 mass%, from the viewpoint of strength development, etc. If the proportion is 8 mass% or more, the long-term strength development is further improved. The proportion of the ferrite phase (4CaO·Al2O3·Fe2O3) in the cement clinker powder is preferably 9 to 12 mass %, more preferably 9.5 to 11.5 mass %, and particularly preferably 10 to 11 mass %, from the viewpoint of strength development and the like.
[0011] In this specification, the proportions of the aluminate phase, alite, belite, and ferrite phase in the cement clinker powder are calculated as percentages in the total amount (100 mass%) of the cement clinker powder based on the chemical components of the cement clinker raw materials and the cement clinker (burned product) using the following Bogue's calculation formulas (1) to (4). (1) Alite (mass %) = (4.07 x CaO (mass %)) - (7.60 x SiO2 (mass %)) - (6.72 x Al2O3 (mass %)) - (1.43 x Fe2O3 (mass %)) (2) B-lite (mass%)=(2.87×SiO2(mass%))-(0.754×C3S(mass%)) (3) Aluminate phase (mass%)=(2.65×Al2O3(mass%))-(1.69×Fe2O3(mass%)) (4) Ferrite phase (mass%) = 3.04 × Fe2O3 (mass%)
[0012] As the raw material for cement clinker, it is possible to use raw materials generally used in the production of cement clinker. Specifically, it is possible to use CaO raw materials such as limestone, quicklime, and slaked lime, silicon-containing raw materials such as silica stone and clay, aluminum-containing raw materials such as clay, and iron-containing raw materials such as iron slag and iron cake. In addition to the above raw materials, one or more materials selected from industrial waste, general waste, and construction waste soil can be used as part of the raw materials. As a method for producing cement clinker, the above-mentioned raw materials are mixed so that the ratios of the aluminate phase, alite, belite, and ferrite phase in the resulting cement clinker are each desired, and the resulting mixture is fired preferably at 1,200 to 1,600°C, more preferably at 1,350 to 1,500°C.
[0013] The Blaine specific surface area of the cement clinker powder is preferably 2,500 to 7,000 cm 2 / g, more preferably 3,000 to 6,000 cm 2 / g, and particularly preferably 3,500 to 5,000 cm 2 / g. The Blaine specific surface area is 2,500 cm 2 If the Blaine specific surface area is 7,000 cm 2 / g or less, the fluidity and workability of mortar and the like containing the mixed cement composition are further improved.
[0014] In the total amount of cement clinker powder, ground granulated blast furnace slag, and limestone powder (100% by mass), the proportion of ground granulated blast furnace slag is 22-43% by mass, preferably 24-41% by mass, more preferably 28-39% by mass, and particularly preferably 32-37% by mass. If the proportion is less than 22% by mass, the strength development decreases. If the proportion exceeds 43% by mass, the effect of reducing the amount of ground granulated blast furnace slag used by using another component (limestone powder) instead of ground granulated blast furnace slag decreases.
[0015] An example of the ground granulated blast furnace slag is pulverized granulated slag obtained by quenching with water and crushing molten slag, which is a by-product of pig iron production in a blast furnace. The ground granulated blast furnace slag preferably has a basicity of 1.7 or more, more preferably 1.75 or more, and particularly preferably 1.8 or more. If the basicity is 1.7 or more, the strength development is further improved. The basicity is calculated using the following formula (5). Basicity = [(CaO + MgO + Al2O3) / SiO2] (5) (The chemical formula in the formula represents the content (%) of the compound represented by the chemical formula in the ground granulated blast furnace slag.)
[0016] The Blaine specific surface area of the ground granulated blast furnace slag is preferably 3,000 to 7,000 cm 2 / g, more preferably 3,500 to 6,000 cm 2 / g, and particularly preferably 4,000 to 5,000 cm 2 / g. The Blaine specific surface area is 2,500 cm 2 If the Blaine specific surface area is 7,000 cm 2 / g or less, the fluidity and workability of mortar and the like containing the mixed cement composition are further improved.
[0017] In the total amount of cement clinker powder, ground granulated blast furnace slag, and limestone powder (100% by mass), the proportion of limestone powder is 4-23% by mass, preferably 6-21% by mass, more preferably 7-20% by mass, even more preferably 8-18% by mass, and particularly preferably more than 10% by mass and 16% by mass or less. If the proportion is less than 4% by mass, the effect of reducing the amount of ground granulated blast furnace slag used by using another component (limestone powder) instead of ground granulated blast furnace slag is reduced. If the proportion exceeds 23% by mass, the strength development decreases.
[0018] The content of calcium carbonate in the limestone powder is preferably 90% by mass or more, more preferably 95% by mass or more. If the content is 90% by mass or more, the strength development is further improved. The limestone powder may be crushed limestone, or may be carbonated powder of ready-mixed concrete sludge or concrete. These powders can fix carbon dioxide gas that would normally be released into the atmosphere.
[0019] The Blaine specific surface area of the limestone powder is preferably 3,000 to 20,000 cm 2 / g, more preferably 3,500 to 18,000 cm 2 / g, and more preferably 4,000 to 15,000 cm 2 / g, and more preferably 4,200 to 10,000 cm 2 / g, and particularly preferably 4,500 to 9,500 cm 2 / g. The Blaine specific surface area is 3,000 cm 2 If the Blaine specific surface area is 20,000 cm2 / g or less, the fluidity and workability of mortar and the like containing the mixed cement composition are further improved.
[0020] The mixed cement composition may contain gypsum for the purpose of adjusting the setting time and improving workability. The amount of gypsum contained in the mixed cement composition is preferably 1.5 to 6.0 parts by mass, more preferably 1.8 to 5.5 parts by mass, and particularly preferably 2.0 to 5.2 parts by mass, in terms of SO3, per 100 parts by mass of cement clinker powder, from the viewpoints of strength development and the fluidity and workability of mortar and the like containing the mixed cement composition. In addition, the proportion of gypsum in the mixed cement composition is preferably 1.5 to 5.0 mass%, more preferably 1.8 to 4.5 mass%, and particularly preferably 2.0 to 4.0 mass%, in terms of SO3, from the viewpoints of strength development and the fluidity and workability of mortar and the like containing the mixed cement composition. Examples of gypsum include natural gypsum dihydrate, flue gas desulfurization gypsum, phosphate gypsum, titanic gypsum, hydrofluoric gypsum, refined gypsum, hemihydrate gypsum, anhydrous gypsum, etc. These may be used alone or in combination of two or more.
[0021] The method for producing the mixed cement composition of the present invention is not particularly limited, and examples thereof include (i) a method in which clinker, blast furnace slag, limestone, and gypsum are mixed while being simultaneously ground, and (ii) a method in which pre-ground cement (a mixture of clinker powder and gypsum), pre-ground granulated blast furnace slag, and pre-ground limestone powder are mixed. In the method (ii), the ground granulated blast furnace slag may contain gypsum (previously mixed with blast furnace slag and gypsum while simultaneously grinding).
[0022] A paste, mortar or concrete can be prepared by mixing the mixed cement composition of the present invention with water, aggregates (fine aggregate, coarse aggregate), and other materials that are mixed as necessary. The mixed cement composition of the present invention has a compressive strength at 7 days measured by the method described in "JIS R 5201:2015 Physical Testing Methods for Cement" of preferably 33 MPa or more, more preferably 33.5 MPa or more, and particularly preferably 34 MPa or more. EXAMPLES
[0023] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [Materials used] (1) Finely ground blast furnace slag; Blaine specific surface area: 4,230 cm 2 / g, density: 2.92g / cm 3 , Basicity: 1.80 (2) Limestone powder A; Blaine specific surface area: 5,130 cm 2 / g, calcium carbonate content: 95% by mass or more, density: 2.72 g / cm 3 (3) Limestone powder B; Blaine specific surface area: 8,840 cm 2 / g, calcium carbonate content: 95% by mass or more, density: 2.72 g / cm 3 (4) Limestone powder C; Blaine specific surface area: 9,020 cm 2 / g, calcium carbonate content: 95% by mass or more, density: 2.72 g / cm 3 [Production of blast furnace slag mixture] The above ground granulated blast furnace slag and gypsum (flue gas desulfurization gypsum) were mixed to produce a blast furnace slag mixture (a mixture of ground granulated blast furnace slag and gypsum) having a gypsum content of 2.0 mass% (SO3 equivalent). [Manufacture of cements A to F] Using the reagent as a raw material, cement clinker was burned in a test kiln, and then the cement clinker, gypsum dihydrate (flue gas desulfurization gypsum), and gypsum hemihydrate were crushed and mixed in a mill to prepare cements A to F (mixtures of cement clinker powder and gypsum) with the mineral composition and Blaine specific surface area shown in Table 1. The hemihydration rate of gypsum was 50% for cements A to C and E, and 76% for cement D. In addition, in preparing cement F, only gypsum dihydrate was used as the gypsum.
[0024] [Table 1]
[0025] [Examples 1 to 11, Comparative Examples 1 to 10] The types of cement shown in Table 2, the blast furnace slag mixture, and limestone powder were mixed in the amounts shown in Table 2 to obtain mixed cement compositions. The compressive strength of the blended cement composition was measured at ages of 3 days, 7 days, and 28 days in accordance with the method described in "JIS R 5201:2015 Physical testing methods for cement." In addition, the mortar flow value of the mixed cement composition was measured by performing a drop motion 15 times in accordance with "JIS R 5201:2015 (Physical testing method for cement)".
[0026] The proportions of cement clinker powder, etc. in the total amount of 100 mass% of the cement clinker powder (represented as "clinker" in Tables 2 to 4), ground granulated blast furnace slag (represented as "blast furnace slag" in Tables 2 to 4), and limestone powder (represented as "limestone" in Tables 2 to 4) contained in the mixed cement composition, and the amount of gypsum (SO3 equivalent value) per 100 parts by mass of the clinker powder are as shown in Tables 2 to 4. The results are shown in Table 2.
[0027] [Table 2]
[0028] [Examples 12 to 19, Comparative Examples 11 to 12] The types of cement shown in Table 3, the blast furnace slag mixture, and the limestone powder were mixed in the amounts shown in Table 3 to obtain a mixed cement composition. The compressive strength and other properties of the obtained mixed cement composition were measured in the same manner as in Example 1. The results are shown in Table 3.
[0029] [Table 3]
[0030] [Example 20] The types of cement shown in Table 4, the blast furnace slag mixture, and the limestone powder were mixed in the amounts shown in Table 4 to obtain a mixed cement composition. The compressive strength and other properties of the obtained mixed cement composition were measured in the same manner as in Example 1. [Examples 21 to 23] A mixture was obtained by mixing the types of cement, blast furnace slag mixture, and limestone powder shown in Table 4. The blending amounts of cement, blast furnace slag mixture, and limestone powder were determined as shown in Table 4. Next, the mixture was mixed with gypsum dihydrate to obtain a mixed cement composition. The amount of gypsum dihydrate (mixed separately from the gypsum contained in the cement and blast furnace slag mixture) to be mixed with the mixture was determined so that the amount of gypsum relative to the cement clinker powder (the total amount of gypsum and gypsum dihydrate contained in the cement and blast furnace slag mixture) was the amount shown in Table 4. The obtained mixed cement composition was measured for compressive strength, etc. in the same manner as in Example 1.
[0031] [Example 24] A mixture was obtained by mixing the types of cement, blast furnace slag mixture, and limestone powder shown in Table 4. The blending amounts of cement, blast furnace slag mixture, and limestone powder were determined as shown in Table 4. Next, the mixture was mixed with dihydrate gypsum and anhydrous gypsum to obtain a mixed cement composition. The amount of dihydrate gypsum and anhydrous gypsum (mixed separately from the gypsum contained in the cement and blast furnace slag mixture) mixed with the mixture was determined so that the amount of gypsum relative to the cement clinker powder (the total amount of dihydrate gypsum and anhydrous gypsum contained in the cement and blast furnace slag mixture) was the amount shown in Table 4, and the proportion of dihydrate gypsum was 72 mass% and the proportion of anhydrous gypsum was 28 mass% in the total amount of dihydrate gypsum and anhydrous gypsum contained in the cement and blast furnace slag mixture, 100 mass%. The compressive strength and the like of the obtained mixed cement composition were measured in the same manner as in Example 1.
[0032] [Example 25] The types of cement shown in Table 4, the blast furnace slag mixture, and the limestone powder were mixed in the amounts shown in Table 4 to obtain a mixed cement composition. The compressive strength and other properties of the obtained mixed cement composition were measured in the same manner as in Example 1. [Examples 26 to 28] A mixed cement composition was obtained in the same manner as in Example 21. For the obtained mixed cement composition, compressive strength and the like were measured in the same manner as in Example 1.
[0033] [Example 29] A mixed cement composition was obtained in the same manner as in Example 24, except that the amounts of gypsum dihydrate and anhydrous gypsum (mixed separately from the gypsum contained in the cement and blast furnace slag mixture) were set to amounts such that the ratio of gypsum dihydrate was 78 mass% and the ratio of anhydrous gypsum was 22 mass% in 100 mass% of the total amount of gypsum, gypsum dihydrate, and anhydrous gypsum contained in the cement and blast furnace slag mixture. The compressive strength and the like of the obtained mixed cement composition were measured in the same manner as in Example 1.
[0034] [Table 4]
[0035] From Tables 2-3, comparing Examples 1-3 and Comparative Examples 1-2, it can be seen that the mortar compressive strengths at 3-7 days of Examples 1-3 (percentage of limestone powder: 10.3-20.5% by mass) (3 days: 21.8-21.9 MPa, 7 days: 34.1-37.0 MPa) are greater than the mortar compressive strengths at 3-7 days of Comparative Examples 1-2 (percentage of limestone powder: 0-2.6% by mass) (3 days: 18.5-21.3 MPa, 7 days: 28.4-32.1 MPa), and are excellent in early strength development. In particular, it can be seen that Examples 1-2 (percentage of limestone powder: 10.3-15.4% by mass) are particularly excellent in early strength development. In addition, when comparing Examples 4 to 7 with Comparative Examples 3 to 4, it is found that the mortar compressive strengths of Examples 4 to 7 (proportion of limestone powder: 5.1 to 20.5% by mass) at ages of 3 to 7 days (3 days: 22.3 to 24.0 MPa, 7 days: 33.8 to 36.3 MPa) are greater than the mortar compressive strengths of Comparative Examples 3 to 4 (proportion of limestone powder: 0 to 2.6% by mass) at ages of 3 to 7 days (3 days: 18.4 to 20.7 MPa, 7 days: 27.3 to 30.1 MPa), and are excellent in early strength development. In particular, it is found that Examples 5 to 6 (proportion of limestone powder: 10.3 to 15.4% by mass) are particularly excellent in early strength development. Similar trends are also seen in comparisons between Examples 8-11 and Comparative Examples 5-6, between Examples 12-15 and Comparative Examples 11-12, and between Examples 16-19 and Comparative Examples 13-14. Also, in Comparative Examples 7 to 10, which used cements D to E with an aluminate phase ratio of 9.1 to 9.3 mass %, the mortar compressive strength at ages of 3 to 7 days was low (3 days: 15.7 to 17.6 MPa, 7 days: 25.2 to 32.8 MPa).
[0036] Furthermore, from Table 4, it can be seen that the mortar compressive strengths (3 days: 22.0-23.0 MPa, 7 days: 34.0-38.5 MPa, 28 days: 51.1-54.6 MPa) of Examples 20-29 (ratio of cement clinker powder: 51.1-51.9 mass%, ratio of ground granulated blast furnace slag: 27.6-38.2 mass%, ratio of limestone powder: 10.4-20.9 mass%) at ages of 3-28 days are comparable to those of Examples 1-19 at ages of 3-28 days. This shows that even if the mixing ratio of cement clinker powder (51.1-51.9 mass%) is low, the early strength development (particularly at ages of 3-7 days) is excellent. In addition, when Examples 20 to 23, which used only gypsum dihydrate, and Example 24, which used gypsum dihydrate and anhydrous gypsum, were compared, it was found that the mortar compressive strengths at ages of 3 to 28 days were similar, and no effect was observed depending on the type of gypsum. A similar tendency was also observed in a comparison between Examples 25 to 28 and Example 29.
Claims
1. A powdery mixed cement composition comprising cement clinker powder, ground granulated blast furnace slag, and limestone powder, In a total amount of 100% by mass of the cement clinker powder, the ground granulated blast furnace slag, and the limestone powder, the proportion of the cement clinker powder is 47 to 59% by mass, the proportion of the ground granulated blast furnace slag is 22 to 43% by mass, and the proportion of the limestone powder is 4 to 23% by mass, In the cement clinker powder, the ratio of the aluminate phase is more than 13 mass% and 17 mass% or less, the ratio of the alite is 54 to 63 mass%, the ratio of the belite is 8 to 17 mass%, and the ratio of the ferrite phase is 9 to 12 mass%, A powdery mixed cement composition comprising 1.5 to 6.0 parts by mass of gypsum, calculated as an SO 3 value, per 100 parts by mass of the cement clinker powder.
2. The Blaine specific surface area of the limestone powder is 3,000 to 20,000 cm 2 The mixed cement composition of claim 1, wherein the .alpha.-zinc content is 1 / g.
3. The mixed cement composition according to claim 1 or 2, wherein the compressive strength at 7 days measured by the method described in "JIS R 5201: 2015 Physical testing method for cement" is 33 MPa or more.
Citation Information
Patent Citations
Cement concrete product and its production
JP1999209159A
Cement composition
JP2012254909A
Manufacturing method of cement clinker
JP2016064940A
Hydraulic composition
JP2016113326A
Cement composition
JP2016183057A